Water stress is a component of cold acclimation process essential for inducing full freezing tolerance in strawberry - Rajashekar, Channa B.; Panda, Manasa (My University, 2014)
The factors involved in cold acclimation process and their role in inducing freezing tolerance were studied in strawberry (Fragaria X ananassa) plants. The results show that low temperature and water stress are two key components of cold acclimation, in that low temperature typically induced water stress in the plants. After a 2-week exposure of plants to 3/1°C (day/night temperature), the leaf water potential decreased markedly to below -1.6 MPa. While both of these components contribute significantly to the induction of freezing tolerance, water stress is a dominant factor in inducing freezing tolerance, contributing roughly to 56% of freezing tolerance acquired by natural cold acclimation. Typical cold acclimation treatment of plants for 2 weeks increased their freezing tolerance by about 14°C to -20.7°C while the same treatment, in the absence of the accompanying water stress, increased their freezing tolerance only by 5°C, which indicates the importance of water stress during cold acclimation. Furthermore, both low temperature and water stress independently induced the orthologs of cold-responsive genes, COR47 and COR78, however, stronger expression of these genes was observed in response to cold acclimating conditions. Thus, these results show that both of these factors are essential elements of cold acclimation process and play an important role in inducing freezing tolerance in strawberry plants.
Keywords: Freezing tolerance; Cold hardening; Cold-responsive genes; Drought